Optimization of Extraction Process and Antibacterial Activity of Bletilla striata Polysaccharides - Li, Qian; Li, Kun; Huang, Shan-Shan; Zhang, Hou-Li; Diao, Yun-Peng (Asian Journal of Chemistry, 2014)
The aim of the study was to optimize the optimal process conditions for extraction of Bletilla striata polysaccharides and its antibacterial activity in vitro. Conventional water extraction and ethanol precipition method with polysaccharide content as an index through single factor investigation and L9(34) orthogonal table was used to optimize extraction conditions, respectively. The test tube double dilution method was chosen for preliminarily screening of the antibacterial activity and the determination of antibacterial mechanism was according to bacterial state changes in electron microscopy observation. The optimal extraction condition was obtained using cold soaking for 6 h prior to extraction, two times 3 h extraction technology, at 90 °C, with a extract-water ratio of 1:15, for purification using concentration of extract to 1:5 (w/v), addition of a 3-fold volume of 95 % ethanol, ethanol content of up to 80 % and polysaccharide content of 53.72 %, in addition, the MIC to S. aureus was 6.25 mg/mL and MBC could reach 12.50 mg/mL, the mechanism may be related with the permeability of cell membrane. The extraction and purification process for Bletilla striata polysaccharides established in this experiment is simpler, more scientific and suitable and Bletilla striata polysaccharides has a obvious inhibition against S. aureus.